Análise da estrutura relacional das patentes: o caso domínio tecnológico no seguimento dos veículos elétricos e híbridos - Assis, Filippo Savoi de (2018)
This work aimed to analyze the relational structure of patents in the automotive sector, especially for electric vehicles. More specifically, the objective was to: identify relevant patents and emerging technologies in the automotive sector; to establish the profile of deposit of patents of the main depositors, referring to the emerging technologies; identify patent relational structure; quantitatively investigate the patents of the major automobile manufacturers; to study the economic relations and patents of the great automakers and to study the technological relations and patents of the great automakers. In this research the network approach was used in conjunction with patent analysis to show the existing relationships within this industry in the construction of innovation, observing the patents deposited by these companies and the cooperation agreements made between them. Data collection was carried out through the analysis of patents of high commercial value in the automotive sector, collected through the Derwent database, collecting 111,094 patents of international patent code (CIP) B60 which refers to vehicles. The data were processed using Vatange Point software for the preparation of lists and data matrices related to specific fields of patents. By compiling the data of lists, matrices and combinations it was possible to create indicators in graphic form or in tables that were built with the help of software Microsoft Excel 2016 and the software Origin. The graphs representing the networks were obtained with the help of Gephi software. From the results, it is emphasized that the theme of electric and hybrid vehicles has become predominant in the sector, with Toyota, Bosch and Nissan companies dominate the total number of patents, and are organized in groups that gravitate around them sharing patents only with companies with strong business links, especially cross-shareholding, formal strategic alliances or joint ventures. Companies like Volkswagen and Honda have a high number of patents, but no technological partnership between automakers. Others, such as Fiat, Ford and General Motors have no patents, but seek to position themselves within cooperative networks in order to remain competitive in the marketplace. There are still companies like Hyundai, which has no patents in the sample analyzed and at the same time does not establish technological alliances. Thus, it was sought to understand how part of the technological capital is distributed by the automotive sector, in order to collaborate for a better understanding of the sector.